«Like a Jerkin, and a Jerkin’s Lining»: Body, Mind, Sartorial Metaphorsrs, and Sexual Imagery in Sterne’s «Tristram Shandy» (ACME, 2017)
The article analyses the relationship between body, mind and soul in Laurence Sterne’s The Life and Opinions of Tristram Shandy, Gentleman (1759-1767). Starting from a famous “sartorial” metaphor, in the third book of the novel, according to which the body-mind relationship is akin to that of a jerkin and its lining, the article deals with the metaphors of the body as garments, which allude to human sexual sphere through puns and double-entendres. Notwithstanding the reference to Stoic doctrines contained in the above-mentioned metaphor and elsewhere in the novel, as for instance in the motto from Epictetus placed as an epigraph at its beginning, the relationship between the human being and his/her soul is often expressed in corporeal terms. This relationship, however, is communicated in ambiguous ways: both as the embodiment of the soul and as the spiritual elevation of the body. Perhaps this ambiguity is conquered by Sterne’s very writing that gives body and soul to man’s desires and needs.